(7x-2)(4x+8)=

Simple and best practice solution for (7x-2)(4x+8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7x-2)(4x+8)= equation:


Simplifying
(7x + -2)(4x + 8) = 0

Reorder the terms:
(-2 + 7x)(4x + 8) = 0

Reorder the terms:
(-2 + 7x)(8 + 4x) = 0

Multiply (-2 + 7x) * (8 + 4x)
(-2(8 + 4x) + 7x * (8 + 4x)) = 0
((8 * -2 + 4x * -2) + 7x * (8 + 4x)) = 0
((-16 + -8x) + 7x * (8 + 4x)) = 0
(-16 + -8x + (8 * 7x + 4x * 7x)) = 0
(-16 + -8x + (56x + 28x2)) = 0

Combine like terms: -8x + 56x = 48x
(-16 + 48x + 28x2) = 0

Solving
-16 + 48x + 28x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '4'.
4(-4 + 12x + 7x2) = 0

Factor a trinomial.
4((-2 + -1x)(2 + -7x)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2

Subproblem 2

Set the factor '(2 + -7x)' equal to zero and attempt to solve: Simplifying 2 + -7x = 0 Solving 2 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -7x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -7x = 0 + -2 -7x = 0 + -2 Combine like terms: 0 + -2 = -2 -7x = -2 Divide each side by '-7'. x = 0.2857142857 Simplifying x = 0.2857142857

Solution

x = {-2, 0.2857142857}

See similar equations:

| 5/6(-6x-12) | | -100=-2(1+7m) | | 32=2y+8 | | 5+5+6+4+x=23 | | 12-3/5x=-27 | | -9-(8-5d)=18 | | N-(50)=-31 | | 4a-2a=-36 | | 2(-4)+2x=-6x-2 | | 3d+8=-17 | | 120+2y=180 | | 10+7+4=10+7+4 | | P+1-2=7 | | 63=3k | | 6(2X-5)-(3-5X)= | | 4(6x+6)= | | 7a+1-3a-5=3[a+1] | | 9cosx+1=8cosx | | 7n-6n=-6 | | 5/7=x/7000 | | Log(2x+1)=3x-2 | | 1(2+3)=2+3 | | (2t+10)(3s)=180 | | (-5x-1)+2x+3=-4x+5 | | 2(-5x+3)-5x-4=-x+58 | | -8(x+5)=-8x-5(x+5) | | Nz-a=bx+d | | 5x+3x+2=10 | | 5x-17=4z-36 | | -1-3(x+2)=-5x-15 | | -8(x+5)=-8x-(x+5) | | 3-5(-x+1)=-x-8 |

Equations solver categories